The prognostic role of micro-RNAs in Head and Neck Cancers: an umbrella review. (30th September 2020) - Mariani, M; Castagna, C; Pastorino, R; Boccia, S
Abstract: Head and neck cancer (HNC) represents the sixth most common cancer and the seventh cause of cancer-related deaths worldwide. Because of HNC high mortality and morbidity a support from the development of new biomarkers and personalized care for patients is needed. The role of micro-RNAs (miRs), as new epigenetic biomarkers, aimed at improving early diagnosis, predicting prognosis and establishing effective cancer therapies, has recently received considerable attention. The aim of this study was to conduct an umbrella review that synthetizes all the findings of systematic reviews already available in literature that investigate the prognostic role of miRs as potential biomarkers in the field of tertiary prevention of HNC. We selected systematic reviews, published in English until December 2019, related to human HNC with meta-analysis of observational studies that reported quantitative prognostic measures, Hazard Ratios (HRs), of Overall Survival (OS) or Disease-Free Survival (DFS). The methodological quality of the included reviews was assessed using the Assessment of Multiple Systematic Reviews AMSTAR 2 tool. Six systematic reviews were included in the umbrella review. The most reported miRNAs were: miR21; the Let7 family (c, d, g), miR17, 18 family, 20a, 29 family, 125b, 375. A total of 4 reviews assessed miR-21 expression in HNC patients, all showing its upregulation. The most frequently studied miR was miR21 which was reported either in the OS and DFS statistical analyses. The OS analysis showed a significant lower prognosis when miR21 was upregulated. It is involved in oncogenic and oncosuppressive cell signals pathways: the overexpression of miR21 was shown to be associated with cell proliferation, migration, invasion and survival. Recently the cumulative effects of sets of miRs has been increasingly studied and they might be stronger predictor of survival than single. The role of miRNAs as a prognostic biomarker specifically in HNC still need to be investigated. Key messages: Some miRs were demonstrated to have as tumor-suppressing and oncogenic roles according to their level of regulation (up/down-regulation) in Head and Neck cancer patients. The role of miRs as prognostic biomarkers in HNC patients still need to be addressed by performing large scale to verify and enhance the power of evidence and clinical utility of these.